Response of photosynthetic efficiency parameters and leaf area index of alternative barley genotypes to increasing sowing density - Rafał Nowak; Małgorzata Szczepanek; Karolina Błaszczyk; Mohammad Bagher Hassanpouraghdam (Scientific Reports)
Abstract Alternative barley genotypes can be a source of genetic variability for breeding and raw material for functional food production. The reaction of these genotypes to diverse sowing densities is unknown. The study aimed to assess the response in physiological characteristics of alternative barley genotypes Hordeum vulgare var. rimpaui and H. v. var. nigricans to increasing sowing density. In a strict field experiment, two barley genotypes and five sowing densities were tested: 250, 300, 350, 400, and 450 grains m-2. Chlorophyll fluorescence indices, relative chlorophyll content (SPAD), and leaf area index (LAI) were assessed. The interaction of the study year, genotype, and sowing density significantly shaped the physiological indices of the canopy. When rainfall was deficient, the plants reduced their leaf area but had higher SPAD and PIabs of the flag leaf. In the year with optimal rainfall, LAI increased with increasing sowing density. In the dry year, PIabs of the flag leaf in H. v. var. rimpaui was the highest at 250 grains m-2 and decreased with increasing density, and in H. v. var. nigricans, it only reduced at 450 grains m-2 A strong negative relationship was observed between LAI and SPAD, as well as between LAI and PIabs. Sowing density had a significant effect on grain yield per plant, which was related to the physiological response. However, the genotypes tested responded differently to this factor. The results may by prove for agricultural practice and scientific research, particularly in relation to the optimal sowing density of alternative barley genotypes and the identification of density-tolerant genotypes in response to varying environmental conditions.